2019
DOI: 10.1002/jpln.201800538
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between greenhouse gas emissions and changes in soil gas diffusivity in a field experiment with biochar and lime

Abstract: Reducing greenhouse gas emissions from arable soil while maintaining productivity is a major challenge for agriculture. Biochar is known to reduce N2O emissions from soil, but the underlying mechanisms are unclear. This study examined the impact of green waste biochar (20 Mg ha−1) and lime (CaCO3; 2 Mg ha−1) application on soil gas transport properties and related changes in these to soil N2O and CO2 emissions measured using automated chambers in a field experiment cropped with maize. In situ soil water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Biochar application reduced soil N 2 O emissions by decreasing the concentrations of soil labile N forms and hindering the activities of N-cycling enzymes (Song et al, 2019). A field study on maize crop in Switzerland reported that the enhanced soil gas diffusivity in biochar added soil (and thus improved soil aeration), may lead to reduced N 2 O emission (Keller et al, 2019). However, Suddick and Six (2013) found no considerable change in N 2 O flux with the application of biochar and compost.…”
Section: Carbon Sequestration and Ghg Emission Reduction With Biochar Applicationmentioning
confidence: 99%
“…Biochar application reduced soil N 2 O emissions by decreasing the concentrations of soil labile N forms and hindering the activities of N-cycling enzymes (Song et al, 2019). A field study on maize crop in Switzerland reported that the enhanced soil gas diffusivity in biochar added soil (and thus improved soil aeration), may lead to reduced N 2 O emission (Keller et al, 2019). However, Suddick and Six (2013) found no considerable change in N 2 O flux with the application of biochar and compost.…”
Section: Carbon Sequestration and Ghg Emission Reduction With Biochar Applicationmentioning
confidence: 99%
“…To determine the soil pore volume, on 12 April 2019, 72 undisturbed cylindrical soil samples (100 cm −3 ) were collected at three depths (3-8, 18-23, and 58-63 cm) with 12 replications at each site and transferred to the laboratory. In the laboratory, different pore diameters were measured following the approach by Keller et al (2019). For this, samples were saturated from below and then drained to soil matric potentials of −30, −60, −100, −300, and −1,500 kPa.…”
Section: Soil Properties and Fertilizer Nutrientmentioning
confidence: 99%
“…Air porosity was calculated based on the difference between volumetric water content (VWC) and total pore volume. The relative gas diffusion coefficient (D p /D 0 ) was calculated based on air-filled porosity by following the approach by Keller et al (2019). A D p /D 0 of 0.02 has been suggested as the critical threshold for adequate soil aeration, and the D p /D 0 value lower than 0.02 indicates insufficient soil aeration (Schjønning et al, 2003).…”
Section: Soil Properties and Fertilizer Nutrientmentioning
confidence: 99%
“…Biochar application reduced soil N 2 O emissions by decreasing the concentrations of soil labile N forms and hindering the activities of N-cycling enzymes [10]. A field study on maize crop in Switzerland reported that the enhanced soil gas diffusivity in biochar added soil (and thus improved soil aeration), may lead to reduced N 2 O emission [11]. However, Suddick and Six [12] found no considerable change in N 2 O flux with the application of biochar and compost.…”
Section: Introductionmentioning
confidence: 99%